2022
DOI: 10.1017/s1092852922000074
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in patients with Tourette syndrome

Abstract: Background Tourette syndrome (TS) is a neurodevelopmental disorder characterized by the presence of motor and phonic tics. It is at least three times more common in males compared with females; however, the clinical phenomenology between sexes has not been fully examined. We aimed to contrast the clinical features between males and females with TS and chronic tic disorder. Methods We studied 201 consecutive patients fulfilling the diagnostic criteria for TS, persistent (or chronic) motor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
29
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 42 publications
3
29
3
Order By: Relevance
“…Another recent study in 201 individuals with tic disorders (age = 4–65 years) found that age at onset and frequency, distribution, and complexity of tics were also similar between sexes. Although mild differences were found in the group of patients younger than 18 years, these authors have suggested that tic severity, tic complexity, and related impairment may be slightly greater with age in women compared to men [28]. However, these small differences between males and females with TS do not allow for the confounding of TS and FTLBs in women, in view of strikingly different presentation and phenomenology (in terms of type and distribution of behaviours, number, frequency, intensity, and complexity) between the two conditions, regardless of sex.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study in 201 individuals with tic disorders (age = 4–65 years) found that age at onset and frequency, distribution, and complexity of tics were also similar between sexes. Although mild differences were found in the group of patients younger than 18 years, these authors have suggested that tic severity, tic complexity, and related impairment may be slightly greater with age in women compared to men [28]. However, these small differences between males and females with TS do not allow for the confounding of TS and FTLBs in women, in view of strikingly different presentation and phenomenology (in terms of type and distribution of behaviours, number, frequency, intensity, and complexity) between the two conditions, regardless of sex.…”
Section: Discussionmentioning
confidence: 99%
“…A second study (n = 148) reported a later onset age in girls, but the mean difference was only 1.2 years [ 25 ]. Most studies, including the largest one [ 33 ], found no significant sex difference in age of onset [ 34 , 35 , 36 , 37 , 38 ]. The only large, prospective study of youth beginning before tic onset found male predominance [ 30 ].…”
Section: Understanding Tourette Syndromementioning
confidence: 99%
“…In summary, later onset in females is possible but unproven, and even the studies that reported a difference in age of onset found small differences, with mean onset by age 10. A recent blinded video review of 201 individuals found a statistically higher frequency of complex tics in males than in females [ 38 ].…”
Section: Understanding Tourette Syndromementioning
confidence: 99%
“…Described differences in phenomenology between sexes have varied between studies. In a recent study of 201 individuals (age 4–65 years) with tic disorders, males younger than 18 years ( n = 118) had a greater complexity and severity of tics than females ( P = 0.049) and an earlier age at onset (mean age 5.9 versus 7.5 years old) 8 . These differences were not present in subjects older than 18.…”
mentioning
confidence: 93%